Edible oil-producing plants in the Sinja Valley, Jumla, Nepal - Khadka, Dipak; Paudel, Hem Raj; Luo, Binsheng; Ding, Mingyan; Basnet, Neha; Bhatta, Sijar; Aryal, Prakash Chandra; Kunwar, Ripu M.; Cui, Dafang; Shi, Shi (Frontiers in Sustainable Food Systems, 2023)
The indigenous people of Nepal have accumulated knowledge of plants and their uses spanning millennia of oral history, but the current sociodemographic trend threatens the transition of this knowledge. Recording the uses and knowledge of these plants is therefore imperative for revitalizing the traditions and culture and the sustainable use and availability of plant species. We interviewed a total of 80 Sinja Valley residents. We calculated the relative frequency of citations (RFC) of recorded edible oil plants. Using the Kruskal-Wallis test and the Wilcoxon test for gender, the difference in the use of edible oil plants mentioned by age group, education level, and occupation of the respondents was determined. These interviews yielded knowledge on 13 different edible oil-producing plant species (EOPPs) including nine indigenous species and six collected from the wild. EOPPs helped effectively treat 19 disorders with Prunus mira being considered a very good treatment for gastritis. Prinsepia utilis was the most common and frequently used (RFC = 0.99) edible oil-producing plant. Most respondents reported that oil-producing and oil-consuming cultures vary and are decreasing among Sinja Valley residents. The locals were subsistence farmers, and the edible oils for their household purposes were prepared using traditional knowledge. However, the tradition is scourged by commercially-available tawdry oil. In rural areas, the knowledge of edible oil-producing plants has been decimated due to outmigration and sociocultural transformation. Edible oil production from indigenous plants should continue for the culture and conservation of rural livelihood.